2016
DOI: 10.3892/ijmm.2016.2845
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 inhibits cancer cell growth and promotes apoptosis

Abstract: Cervical cancer is one of the most common causes of cancer-related mortality in women in developing countries. Interferon (IFN)-α has been widely used in the treatment of various types of cancer, including cervical cancer, and IFN-stimulated gene 15 (ISG15), an ubiquitin-like protein, is upregulated by IFN-α treatment. The anti-virus and antitumor effects of ISG15 have been reported; however, its mechanism of action have not yet been fully elucidated. In this study, HeLa cells were used as a model system to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
(41 reference statements)
1
30
0
Order By: Relevance
“…Previous studies confirmed that p53 was one of the most commonly mutation genes in cancer ( 30 32 ). Additionally, the upregulation of p53 in cancer cells may prevent cancer cell proliferation by promoting cell cycle arrest and apoptosis ( 33 36 ). Liu et al ( 37 ) revealed that the p53 pathway in human cervical cancer cells is activated by reversion-inducing-cysteine-rich protein with Kazal motifs overexpression, which induces cancer cell apoptosis and reduces migration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that p53 was one of the most commonly mutation genes in cancer ( 30 32 ). Additionally, the upregulation of p53 in cancer cells may prevent cancer cell proliferation by promoting cell cycle arrest and apoptosis ( 33 36 ). Liu et al ( 37 ) revealed that the p53 pathway in human cervical cancer cells is activated by reversion-inducing-cysteine-rich protein with Kazal motifs overexpression, which induces cancer cell apoptosis and reduces migration.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ISG15 is involved in anti-viral pathways and ISG15-deficient mice are highly susceptible for viral infections like herpes or influenza [ 170 , 171 ]. In general, ISG15 is an important type I interferon (IFN) effector system.…”
Section: Regulation Of Beclin 1 Via Distinct Ubiquitination Machinmentioning
confidence: 99%
“…The result showed the statistically most significant differences in cell cycle and apoptosis. Previous reports found that (Zhou et al, 2017;Park et al, 2000;Smith, 2015;Yang et al, 1997) Il2, Bcl2, Stat2, Isg15, Oasl2 may participate in the cell survival and anti-apoptosis processes, and these genes were found to be quantitatively different in the culture with B6 DCs and IL-2-deficient DCs by real time PCR (Fig. 5D).…”
Section: Il-2 + DC Contact Leads To An Altered Gene Expression Profilementioning
confidence: 67%